The fifth term of an ap of n terms whose sum is n^2-2n
Answers
Answered by
4
Answer:
7
Step-by-step explanation:
S1 = (1)^2 - 2*1 = 1-2 = -1
S2 = (2)^2 -2*2 = 0
S3 = (3)^2 -2*3 = 9-6 = 3
S4 = (4)^2 - 2*4 = 16-8 = 8
S1 = A1 = -1
A2 = S2 - S1 = 0-(-1) = 1
A3 = S3 - S2 = 3 -0 = 3
A4 = S4 - S3 = 8-3 = 5
here
A1 = -1
d = 2
a5 = -1 + (5-1) *2
A5 = -1 + 8 = 7
Answered by
1
Answer:
first term is 1"2-2*1=-1
s2=a1+a2=4-4=0
a2=1
s.d.=2
a5=-1+4*2=7
hope it helps you
Similar questions
Social Sciences,
7 months ago
Math,
7 months ago
History,
7 months ago
Math,
1 year ago
Science,
1 year ago